LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION IN TRICHIURUS LEPTURUS LINNAEUS - Narasimham, K A (Indian Journal of Fisheries, 2011)
The length-weight relationship and the relative condition in the ribbon fish Trichiurus lepturus were studied in 185 males in the size range 355-960 mm and 143 females in the size range 352-1090 mm collected during the period August 1966 to May 1969. Analysis of covariance of the two regressions showed no significant difference in the slopes. Apparently the sexual cycle does not seem to affect the relative condition of the fish, at least directly, while high intensity of feeding influences the K„ There is a sudden fall in the value of relative condition at 625 mm fish length, and maturity studies indicate that over 90% of fish attained sexual maturity at this length.